Internet Addiction and Sleep Quality in Students of SMA Negeri (Public Senior High School) 9 Manado - Sinadia, Juan Gabriel Claudio; Sarajar, Dewita Karema (Ridwan Institute, 2024)
Sleep is vital for cell regeneration and repair in the human body. Adequate sleep, typically 7-8 hours per day, is crucial for adolescents, as its deficiency can impact various aspects of their lives including physical health, academic performance, school activities, and concentration. However, numerous factors, such as internet addiction, can disrupt sleep quality. Internet addiction, characterized by excessive and uncontrollable internet usage, is particularly prevalent among adolescents and has been linked to sleep disturbances. This study aimed to investigate the relationship between internet addiction and sleep quality among students at SMA N 9 Manado (Public Senior High School). Employing quantitative research methods and correlation analysis, data were collected from 110 active students at SMA N 9 Manado using quota sampling techniques. The Internet Addiction Test (IAT) and the Pittsburgh Sleep Quality Index (PSQI) were utilized as measurement scales. Statistical analyses including the Kolmogorov-Smirnov test, one-way ANOVA test, and Pearson's Product-Moment correlation coefficient were performed. The findings revealed a significant positive correlation (r = 0.533, p < 0.05) between internet addiction and sleep quality among students at SMA N 9 Manado, indicating that higher levels of internet addiction were associated with poorer sleep quality. This underscores the need for interventions aimed at reducing internet addiction among students, with an emphasis on fostering self-awareness regarding internet usage behaviors. Such interventions hold promise for improving the sleep quality and overall well-being of adolescents.